Mikrogeograficzna segmentacja rynku w badaniu stylu życia - Kaczmarek, Mirosława (Microgeographic Market Segmentation in the Study of Lifestyle, 2006)
Microgeographic segmentation is based on the premise that people with similar social status a lifestyle and, therefore, similar consumers' behaviour, live close to one another. Such small spatial units may consist of streets, blocks of flats and also of individual houses. As a result, micro-geographic segmentation may be conducted on various levels of spatial aggregation and its cognitive value grows together with the decrease in size of the spatial unit it concerns. The article presents the results of segmentation of the inhabitants of Poznan conducted with regard to the building type they live in. The segmentation was carried with respect to the way of spending one's free time.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 465-470